471 DEVELOPMENTAL REGULATION OF ERYTHROPOIETIN GENE EXPRESSION THROUGH METHYLATION. (1st January 2006) - Padilla, M. T.; Dai, A.; Palmisano, W.; Ohls, R. K.
Abstract : Erythropoiesis in the fetus is marked by a constant and significant need for increased red blood cells. Although the mechanism of erythropoietic regulation in adults has been investigated and determined to a significant degree, it is unclear if the same mechanism of erythropoietic regulation exists in the fetus. In order to determine if methylation plays a role in differentially inhibiting gene expression of Epo in these tissues during development, we investigated the methylation patterns of the enhancer region of the Epo gene in the mid-trimester human fetal liver and kidney using combined bisulfite restriction analysis (COBRA). DNA was isolated from fetal liver and kidney at 10-22 weeks' gestation and bisulfite modified. For comparision, DNA was also isolated from Hep3B cells to act as a positive control. The methylation status of the Epo enhancer regions was determined using primers that recognize the bisulfite-modified DNA template but did not discriminate between methylated and unmethylated alleles. The 199 bp PCR product from each tissue sample was amplified, purified from gel, ligated into a vector, cloned, and sequenced. The percent methylation of the enhancer region was determined for 5 clones from each tissue type: early (10-11 weeks) and late (20-21 weeks) fetal kidney and liver and Hep 3B cells. The enhancer region of the Epo gene from Hep3B cells was 94% unmethylated, allowing for up-regulation of Epo gene transcription under hypoxic conditions, consistently seen with these cells. Early-gestation fetal liver was 64% unmethylated, while early kidney was 40% unmethylated. Later-gestation fetal tissue showed a greater degree of methylation (Figure). These data are consistent with tissue hypoxia experiments, where early gestation tissue responded to hypoxia better than late gestation and liver responded better than kidney. We speculate that methylation in the enhancer region of the fetal Epo gene plays a role in inhibiting up-regulation under hypoxic conditions in vivo.